What has scripting ever done for us? The CSD Python application programming interface (API) - Sykes, Richard A.; Johnson, Natalie T.; Kingsbury, Christopher J.; Harter, Jürgen; Maloney, Andrew G. P.; Sugden, Isaac J.; Ward, Suzanna C.; Bruno, Ian J.; Adcock, Stewart A.; Wood, Peter A.; McCabe, Patrick; Moldovan, Alexandru A.; et al. (Journal of applied crystallography, 2024)
Since its first release in 2016, the Cambridge Structural Database Python application programming interface (CSD Python API) has seen steady uptake within the community that the Cambridge Crystallographic Data Centre serves. This article reviews the history of scripting interfaces, demonstrating the need, and then briefly outlines the technical structure of the API. It describes the reach of the CSD Python API, provides a selected review of its impact and gives some illustrative examples of what scientists can do with it. The article concludes with speculation as to how such endeavours will evolve over the next decade. An illustration is given of the use of the Cambridge Structural Database (CSD) Python API in the community with some example cases.